Low intracellular magnesium in patients with acute pancreatitis and hypocalcemia. - Ryzen, E. (1990)
To determine the role of magnesium deficiency in the pathogenesis of hypocalcemia in acute pancreatitis, we measured magnesium levels in serum and in peripheral blood mononuclear cells in 29 patients with acute pancreatitis, 14 of whom had hypocalcemia and 15 of whom had normal calcium levels. Only six patients had overt hypomagnesemia (serum magnesium less than 0.70 mmol per liter [1.7 mg per dl]). The mean serum magnesium concentration in hypocalcemic patients was not significantly lower than in normocalcemic patients, but the mononuclear cell magnesium content in hypocalcemic patients with pancreatitis was significantly lower than in normocalcemic patients with pancreatitis (P less than .01). The serum magnesium level did not correlate with that of serum calcium or the mononuclear cell magnesium content, but the latter did significantly correlate with the serum calcium concentration (r = .81, P less than .001). Most patients with hypocalcemia had a low intracellular magnesium content. Three normomagnesemic, hypocalcemic patients with alcoholic pancreatitis also underwent low-dose parenteral magnesium tolerance testing and showed increased retention of the magnesium load. We conclude that patients with acute pancreatitis and hypocalcemia commonly have magnesium deficiency despite normal serum magnesium concentrations. Magnesium deficiency may play a significant role in the pathogenesis of hypocalcemia in patients with acute pancreatitis.